Tensile properties and morphology of fly ash filled recycled Poly(vinyl chloride) / Acrylonitrile Butadiene rubber blends - Supri, A. Ghani (Universiti Malaysia Perlis, 2010)
The effect of filler loading of fly ash (FA) on tensile properties and morphological of recycled poly (vinyl chloride) / acrylonitrile butadiene rubber blends were studied. The micrographs of tensile fracture surfaces of the blend composites were investigated using scanning electron microscopy (SEM). The blends were prepared at 1500C and the rotor speed of 50 rpm in an internal mixer. It was found that the presence of fly ash decreased the tensile strength and elongation at break, and they both decreased with increasing loadings of fly ash. Morphological observations show that the weak filler matrix interaction as there were be more impurities presented at higher fly ash loading which would cause the fly ash to become inactive chemically.